2022
DOI: 10.3389/fragi.2022.927630
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis dysfunction in the process of aging and age-related diseases

Abstract: In this review, we discuss in detail the most relevant proteolytic systems that together with chaperones contribute to creating the proteostasis network that is kept in dynamic balance to maintain overall functionality of cellular proteomes. Data accumulated over decades demonstrate that the effectiveness of elements of the proteostasis network declines with age. In this scenario, failure to degrade misfolded or faulty proteins increases the risk of protein aggregation, chronic inflammation, and the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 151 publications
1
16
0
Order By: Relevance
“…In the last years, we have shown that xenobiotics such as mercury, lead, and fluoride, have an interesting ability to modulate the proteostasis system [ 52 , 53 , 66 , 67 ]. One complex involved in proteostasis is the ubiquitin-proteasome, which regulates the degradation of proteins, along with the Heat Shock Proteins (HSP), which also work on the degradation process, but have special functions in preventing the misfolding of proteins that could lead to the formation of protein aggregates [ 68 , 69 ]. Our proteomic approach showed the up-regulation of HSP-70 kDa (P0DMW0, P0DMW1, and P14659) and HSP-90 KDa subunits (P34058 and P82995).…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, we have shown that xenobiotics such as mercury, lead, and fluoride, have an interesting ability to modulate the proteostasis system [ 52 , 53 , 66 , 67 ]. One complex involved in proteostasis is the ubiquitin-proteasome, which regulates the degradation of proteins, along with the Heat Shock Proteins (HSP), which also work on the degradation process, but have special functions in preventing the misfolding of proteins that could lead to the formation of protein aggregates [ 68 , 69 ]. Our proteomic approach showed the up-regulation of HSP-70 kDa (P0DMW0, P0DMW1, and P14659) and HSP-90 KDa subunits (P34058 and P82995).…”
Section: Discussionmentioning
confidence: 99%
“…Because cellular compensation mechanisms decline with aging. [4,5] Decompensation of cellular homeostasis occurs late in life because of an aging-associated decline in homeostasis mechanisms, either of synthesis, maintenance, or degradation (Figure 1). Here, I would like to propose a two-hit hypothesis of neurodegeneration that could explain the late onset of neurodegenerative diseases of the aging brain.…”
Section: F I G U R Ementioning
confidence: 99%
“…The other compartments of proteostasis-maintenance involving the chaperone system and mitochondria and finally degradation by the ubiquitin/proteasome system or micro/macroautophagy/lysosomal system-are also subject to functional decline during aging. [4,5,65] Thereby, all three compartments of proteostasis are affected by cellular aging, synthesis, maintenance and degradation. Maintenance and degradation constitute the "buffering" capacity of cells, that is, the ability to cope with proteotoxic stress.…”
Section: Cellular Proteostasis Declines During Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that proteasome dysfunction induces ER stress through decreased degradation of denatured proteins. Diabetes, neurodegenerative diseases, metabolic diseases, cancer, and hypertension are closely related to ER stress associated with aging and genetic factors [ 1 ]. Recently, in skeletal muscle tissue, increased ER stress has been reported in myopathies, such as muscular dystrophy and inclusion body inflammation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%